Penerapan Metode Diskusi Terhadap Peningkatan Hasil Belajar PAI di Kelas XI F.1 SMAN 2 Padang - Lativa Martatilova (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) through the implementation of the discussion method in class XI F.1 at SMAN 2 Padang. This research employed a Classroom Action Research (CAR) approach conducted over two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observations, written tests, interviews, and documentation. The results showed that implementing the discussion method significantly increased student engagement in the learning process and their learning outcomes. In the first cycle, the students' mastery level reached 55%, which improved to 66.67% in the second cycle. This improvement indicates that the discussion method effectively encouraged students to actively participate, think critically, and gain a deeper understanding of the material. This research provides a positive contribution to developing interactive and collaborative learning strategies in Islamic Religious Education.